2020
DOI: 10.1016/j.heliyon.2020.e04313
|View full text |Cite
|
Sign up to set email alerts
|

Sub-acute toxicity study of methanol extract of Tetrorchidium didymostemon leaves using biochemical analyses and gene expression in Wistar rats

Abstract: Tetrorchidium didymostemon is widely used by traditional medicine practitioners to manage and treat several diseases. Despite its known ethnomedicinal uses, there are no scientific studies on the toxic effects of this plant. This study was performed to evaluate the potential toxicity of methanol extracts Tetrorchidium didymostemon leaves through sub-acute oral administration in rats. Twenty four (24) male albino rats (Wistar strain) of average weight 150 AE 20 g were randomly divided into 4 groups of 6 rats ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Changes in body weight provide information about the effects of a substance administered. 13 Liver and kidney are major target organs for several substances due to their critical role in various body processes including detoxification and excretion. 24 In this respect, it's critical that studies examining the biochemical effects of substances take a close look at the status of these organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in body weight provide information about the effects of a substance administered. 13 Liver and kidney are major target organs for several substances due to their critical role in various body processes including detoxification and excretion. 24 In this respect, it's critical that studies examining the biochemical effects of substances take a close look at the status of these organs.…”
Section: Discussionmentioning
confidence: 99%
“…This subacute toxicity study was designed with slight modification based on earlier procedure of Ebohon et al (2020). 13 The rats were left in their cages under observation during the period of study for mortality and any signs of toxicity such as gross behavioral, neurologic, and autonomic toxic signs such as changes in respiration, heart rate, salivation, lacrimation, drowsiness, or convulsions.…”
Section: ×100%mentioning
confidence: 99%
“…The liver and kidneys play an important role in detoxification and excretion in the body ( Ebohon et al., 2020 ). Therefore, liver and kidney function tests are necessary and reliable for toxicity studies.…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA isolation, cDNA conversion, PCR amplification and agarose gel electrophoresis was done following the method described by Omotuyi et al [23] as reported by Ebohon et al [24]. Primers targeting exon-exon junction was designed using Primer3 software [25].…”
Section: Total Rna Isolation Cdna Conversion and Pcr Amplificationmentioning
confidence: 99%